Neuroblastoma With Opsoclonus-Myoclonus-Ataxia Syndrome: Role of Chemotherapy in the Management. Issue 7 (October 2021) - Anand, Sachit; Agarwala, Sandeep; Jain, Vishesh; Bakhshi, Sameer; Dhua, Anjan; Gulati, Sheffali; Seth, Rachna; Srinivas, Maddur; Jana, Manisha; Kandasamy, Devasenathipathy; Bhatnagar, Veereshwar
Abstract : Children with neuroblastoma (NB) and opsoclonus-myoclonus-ataxia syndrome (OMAS) have a favorable oncologic outcome and overall survival. In contrast, despite intensive multidrug immunomodulation, the neurologic outcome is complicated by the relapsing nature of the neurologic symptoms and long-term neurobehavioral sequelae. Being associated with low-risk NB, there exists an ambiguity in the current literature regarding the administration of chemotherapy in these children. We reviewed our archives for children with NB-OMAS over a 22-year (January 1996 to January 2018) period. Eighteen children (10 female) with a median age at diagnosis of 23 months had NB-OMAS and were included. They had stage 1 (9/18; 50%), 2 (1/18; 5.5%), 3 (7/18; 39%), and 4 (1/18; 5.5%) disease according to the International Neuroblastoma Staging System. Multimodality therapy included surgery (16/18; 89%), chemotherapy (11/18; 61%), and immunomodulatory therapy (10/18; 55%). Complete oncologic remission was achieved in all children. Relapse of OMAS and presence of neurologic sequelae were observed in 1 (5.5%) and 5 (28%) cases, respectively. Presence of neurologic sequelae was significantly associated with low-tumor stage ( P =0.036) and treatment without chemotherapy ( P =0.003). Chemotherapy administration was the only variable significantly predicting a favorable neurologic outcome (95% confidence interval: 0.26-1.40, P =0.01). To conclude, our study including a limited cohort of patients highlights a favorable neurologic outcome associated with chemotherapy administration in children with NB-OMAS. However, further studies with larger sample size need to be conducted before drawing any definite conclusions. Abstract : Supplemental Digital Content is available in the text.